Preparation method of honeycomb micron-sized porous silicon material

By combining sodium alginate solution with directional ion gelation and freeze-drying, the problem of porous silicon material size regulation is solved, and a honeycomb micron-scale porous silicon material with high mechanical properties and stability is prepared, achieving simplification of the process and improve safety.

CN119284910APending Publication Date: 2025-01-10UNIV OF SCI & TECH BEIJING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411243040.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing methods for preparing porous silicon materials have problems such as narrow pore size distribution, difficulty in regulation, high cost, complex process, poor safety and insufficient mechanical strength stability, especially lack of effective preparation methods in the micropore range.

Method used

The sodium alginate solution is used to form honeycomb pores during directional ion gelation, and a honeycomb micron-scale porous silicon material is prepared in combination with the freeze-drying method, so as to achieve precise control of pore size by changing the type and concentration of the gel agent.

Benefits of technology

A regular arrangement of honeycomb micron-scale through-porous silicon material has been obtained, with high porosity and adjustable pore size, which improves mechanical performance and stability, simple process and high safety, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284910A_ABST
    Figure CN119284910A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a honeycomb micron-sized porous silicon material, and belongs to the technical field of inorganic non-metallic material preparation. The preparation method comprises the following steps: obtaining sodium alginate sol in which nanoscale silicon powder is stably suspended through a ball milling process, transferring the sol into a mold, spraying a metal ion solution gel on the top of the sol for directional gelatinization, demolding after the gelatinization is completed to obtain a wet blank, replacing metal ions from the wet blank in an acid environment, and freeze-drying the wet blank, so as to obtain the sodium alginate / metal ion composite material. And carrying out heat preservation and glue removal at a high temperature to obtain the honeycomb-shaped micron-sized porous silicon material. By adjusting the variety and concentration of the gels, the large-range accurate regulation and control of the pore size of the porous silicon material can be realized. The porous silicon material prepared by the invention has a highly regular honeycomb structure, good mechanical properties, completely through pores and a wide application prospect in the fields of energy storage, filtration, catalysis, biological medicine and the like, and the pore size can be accurately regulated and controlled in a range of 10-300 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic material preparation, and in particular relates to a method for preparing a honeycomb micron-level porous silicon material. Background Art

[0002] Porous silicon materials have the characteristics of large specific surface area, strong chemical activity, low mass density, high energy density and good biocompatibility. They are widely used in energy storage, filtration, adsorption, catalysis, biomedicine and other fields. The preparation methods of porous silicon materials mainly include electrochemical etching, chemical corrosion, sol-gel method and template method. At present, the preparation methods of porous silicon have the following limitations: (1) The pore size is mainly concentrated in the range of nanopores (1-10nm) and mesopores (10-500nm), and there is little research on micropores (>1μm); (2) Due to the need to introduce corrosive agents, sacrificial templates and alloy precursors, the preparation method has the problems of high cost, complex process, difficulty in large-scale production and poor safety; (3) The pore size distribution is narrow, the pore size is not easy to control, and the pore structure has poor connectivity; (4) The mechanical strength, stability and durability under specific environments need to be improved.

[0003] The honeycomb structure in nature has the advantages of large specific surface area, high mechanical strength, high stability and high material utilization. Introducing the honeycomb structure into porous silicon materials is expected to solve the above-mentioned problems in the field. The sodium alginate gel method is an effective process for preparing a honeycomb pore structure. It has been used to prepare porous ceramic materials such as alumina and silicon nitride, but has not yet been used to prepare porous silicon materials. Patent CN103274704B discloses two methods for regulating the pore size of porous ceramic materials by sodium alginate gel process: one is to regulate by changing the content of ceramic powder in the slurry, but this method cannot regulate the pore size alone while keeping the porosity and pore wall thickness unchanged; the second is to regulate by changing the molar fraction ratio of the M unit and the G unit in the sodium alginate molecule, but the process is complicated and cannot achieve precise regulation of the pore size. Therefore, finding an effective preparation method for micron-level porous silicon materials and a precise regulation method for the pore size is a technical problem that needs to be solved urgently for porous silicon materials. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a method for preparing a honeycomb micron-sized porous silicon material. Sodium alginate solution is used to form honeycomb pores in the process of directional ion gelation, and the honeycomb arrangement of silicon powder is realized at the same time. The water in the hydrogel is removed by freeze drying, and the honeycomb micron-sized porous silicon material is obtained after high-temperature debinding. The pore size can be precisely controlled over a wide range by changing the type and concentration of the gelling agent.

[0005] The technical solution of the present invention is:

[0006] A method for preparing a honeycomb micron-sized porous silicon material, characterized in that it comprises the following steps:

[0007] Step 1) adding sodium alginate to deionized water and stirring for 1 to 2 hours to completely dissolve the sodium alginate to obtain a sodium alginate sol;

[0008] Step 2) adding silicon powder and a suspending agent to the sodium alginate sol, and ball milling for 3 to 6 hours to obtain a slurry in which silicon powder is stably suspended;

[0009] Step 3) injecting the slurry obtained in step 2) into a mold, introducing a sufficient amount of gelling agent on the upper surface of the slurry, and demolding after gelation is completed to obtain a wet blank;

[0010] Step 4) washing the wet blank obtained in step 3) in deionized water to remove unreacted metal ions, soaking the wet blank in a gluconolactone solution for 6 to 12 hours to allow hydrogen ions to replace the metal ions involved in the reaction, washing the wet blank with deionized water to remove unreacted hydrogen ions, and freeze-drying the wet blank to obtain a porous silicon dry blank;

[0011] Step 5) The dry blank obtained in step 4) is subjected to high temperature debinding to obtain a porous silicon material.

[0012] Furthermore, in step 1), the concentration of sodium alginate in the solution is 0.5-3%.

[0013] Furthermore, in step 1), the stirring is performed using a magnetic stirrer at a temperature of 50-60°C.

[0014] Furthermore, in step 2), the particle size of the silicon powder is 0.1-1 μm, and the content of the silicon powder in the sol is 0.5-20%.

[0015] Furthermore, the ball milling in step 2) is performed at room temperature at a rotation speed of 200 to 300 rpm.

[0016] Furthermore, the type of the suspending agent in step 2) is one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyacrylate and silane coupling agent, and preferably the mass of the suspending agent is 5-10% of the mass of the silicon powder.

[0017] Furthermore, the gelling agent in step 3) is one or more of calcium chloride, zinc chloride, copper sulfate, nickel chloride, nickel nitrate, cobalt chloride and ferrous chloride solution, the solution concentration is 0.05-10 mol / L, and the gelling reaction time is 3-12 h.

[0018] Furthermore, the freeze-drying process conditions in step 4) are a temperature of -65 to -50°C, a vacuum degree of less than 1 Pa, and a freeze-drying time of 24 to 48 hours.

[0019] The concentration of the gluconolactone solution in step 4) is 0.5-1 mol / L.

[0020] Furthermore, the high-temperature debinding process in step 5) is carried out in a tubular furnace or a vacuum heat treatment furnace, the debinding atmosphere is an inert gas circulation or a vacuum environment, the debinding temperature is 600-650°C, the debinding time is 3-5h, and the heating and cooling rates are 1-2°C / min.

[0021] Furthermore, the pore size of the porous silicon material is regulated by adjusting the type of gelling agent, specifically by selecting one of calcium ion salt solution, copper ion salt solution, divalent cobalt ion salt solution, ferrous ion salt solution, nickel ion salt solution, and zinc ion salt solution, or by selecting more than one solution in combination as the gelling agent, wherein the pore sizes of the porous silicon material prepared by different ion gelling agents of the same concentration are arranged from large to small as follows: calcium ion>nickel ion>divalent cobalt ion>zinc ion>ferrous ion>copper ion; the pore size of the porous silicon material is regulated by adjusting the concentration of the gelling agent, specifically by increasing the concentration of the gelling agent to reduce the pore size of the porous silicon and increase the pore density per unit area.

[0022] A honeycomb micron-sized porous silicon material is characterized in that the porous silicon material is prepared by the method of the present invention, the porous silicon material has regularly arranged honeycomb micron-sized through holes, a porosity of 30-95%, and a pore size range of 10-300 μm.

[0023] Compared with other technologies, the outstanding advantages of the present invention are:

[0024] Honeycomb-shaped micron-scale porous silicon material was prepared by the directional ion gel reaction of sodium alginate solution. The regular hexagonal honeycomb structure can effectively improve the mechanical properties and stability of the porous silicon material.

[0025] The pores of the porous silicon material prepared by this method are all through holes, which has significant advantages in the fields of sewage filtration, biomedicine, chemical catalysis, etc.

[0026] The pore size of porous silicon materials is easy to control. By simply changing the type and concentration of the gelling agent, the pore size can be precisely controlled over a wide range to meet application requirements in different scenarios.

[0027] Compared with porous silicon material preparation processes such as electrochemical etching, chemical corrosion, template method and sol-gel method, this method does not require the use of hazardous chemical reagents, has good safety, simple process, low cost, and is easy to prepare on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings used in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 1 of the present invention;

[0030] Figure 2 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 2 of the present invention;

[0031] Figure 3 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 3 of the present invention;

[0032] Figure 4 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 4 of the present invention;

[0033] Figure 5 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 5 of the present invention;

[0034] Figure 6 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 6 of the present invention;

[0035] Figure 7 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 7 of the present invention;

[0036] Figure 8 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 8 of the present invention;

[0037] Fig. 9 This is a scanning electron microscope surface image of the porous silicon material prepared in Example 9 of the present invention. DETAILED DESCRIPTION

[0038] The specific implementation methods of the present application are described in detail below with reference to the accompanying drawings. It should be noted that the technical features or combinations of technical features described in the following embodiments should not be considered isolated, and they can be combined with each other to achieve better technical effects.

[0039] A method for preparing a honeycomb micron-sized porous silicon material, characterized in that it comprises the following steps:

[0040] Step 1) adding sodium alginate to deionized water, stirring with a magnetic stirrer at 50-60° C. for 1-2 hours to completely dissolve the sodium alginate, and obtaining a sodium alginate sol;

[0041] Step 2) adding silicon powder and a suspending agent to the sodium alginate sol, and ball milling at room temperature at a speed of 200 to 300 rpm for 3 to 6 hours to obtain a slurry in which silicon powder is stably suspended;

[0042] Step 3) injecting the slurry obtained in step 2) into a mold, introducing a sufficient amount of gelling agent on the upper surface of the slurry, and demolding after gelation is completed to obtain a wet blank;

[0043] Step 4) The wet blank obtained in step 3) is washed in deionized water to remove unreacted metal ions, and the wet blank is immersed in a 0.5-1 mol / L gluconolactone solution for 6-12 hours to allow hydrogen ions to replace the metal ions involved in the reaction, and the wet blank is then washed with deionized water to remove unreacted hydrogen ions, and the wet blank is freeze-dried to obtain a porous silicon dry blank;

[0044] Step 5) The dry blank obtained in step 4) is subjected to high temperature debinding to obtain a porous silicon material.

[0045] In this process, debinding refers to keeping the material warm for a period of time under certain temperature and atmosphere conditions to volatilize and discharge organic matter (the organic matter here refers to alginate, polyvinyl pyrrolidone, etc.).

[0046] Example 1

[0047] Take 2g of sodium alginate and add it to 100mL of deionized water. Stir it magnetically at 50℃ for 2h to completely dissolve the sodium alginate and obtain a sol. Add 5g of silicon powder with a particle size of 500nm and 0.5g of polyvinyl pyrrolidone to the sol, and ball mill it at room temperature at a speed of 250rpm for 4h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 5mL of 0.1mol / L calcium chloride solution on the upper surface of the slurry to form a stable film, and then pour 200mL of 0.1mol / L calcium chloride solution on the top of the film, let it stand for 10h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in 1mol / L gluconolactone solution for 8h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a tubular furnace, heated to 620°C at a rate of 2°C / min under argon flow, kept warm for 4 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and its surface image is shown in the figure. Figure 1 As shown, the pore size is approximately 200 μm.

[0048] Example 2

[0049] Take 1g of sodium alginate and add it to 50mL of deionized water. Stir it magnetically at 50℃ for 2h to completely dissolve the sodium alginate and obtain a sol. Add 2.5g of silicon powder with a particle size of 500nm and 0.25g of polyvinyl pyrrolidone to the sol, and ball mill it at room temperature at a speed of 250rpm for 4h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 5mL of 0.1mol / L nickel nitrate solution on the upper surface of the slurry to form a stable film, and then pour 100mL of 0.1mol / L nickel nitrate solution on the top of the film, let it stand for 9h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in 1mol / L gluconolactone solution for 8h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a tubular furnace, heated to 600°C at a rate of 2°C / min under argon flow, kept warm for 3 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and its surface image is shown in FIG. Figure 2 As shown, the pore size is approximately 170 μm.

[0050] Example 3

[0051] Take 1g of sodium alginate and add it to 50mL of deionized water. Stir it magnetically at 50℃ for 2h to completely dissolve the sodium alginate and obtain a sol. Add 2.5g of silicon powder with a particle size of 500nm and 0.25g of polyvinyl pyrrolidone to the sol, and ball mill it at room temperature at a speed of 250rpm for 4h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 5mL of 0.1mol / L cobalt chloride solution on the upper surface of the slurry to form a stable film, and then pour 100mL of 0.1mol / L cobalt chloride solution on the top of the film, let it stand for 8h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in 1mol / L gluconolactone solution for 8h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a tubular furnace, heated to 600°C at a rate of 2°C / min under argon flow, kept warm for 3 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and its surface image is shown in FIG. Figure 3As shown, the pore size is approximately 150 μm.

[0052] Example 4

[0053] Take 1g of sodium alginate and add it to 50mL of deionized water. Stir it magnetically at 50℃ for 2h to completely dissolve the sodium alginate and obtain a sol. Add 2.5g of silicon powder with a particle size of 500nm and 0.25g of polyvinyl pyrrolidone to the sol, and ball mill it at room temperature at a speed of 250rpm for 4h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 5mL of 0.1mol / L zinc chloride solution on the upper surface of the slurry to form a stable film, and then pour 100mL of 0.1mol / L zinc chloride solution on the top of the film, let it stand for 8h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in 1mol / L gluconolactone solution for 8h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a tubular furnace, heated to 600°C at a rate of 2°C / min under argon flow, kept warm for 3 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and its surface image is shown in FIG. Figure 4 As shown, the pore size is approximately 120 μm.

[0054] Example 5

[0055] Take 2g of sodium alginate and add it to 100mL of deionized water. Stir it magnetically at 50℃ for 2h to completely dissolve the sodium alginate and obtain a sol. Add 5g of silicon powder with a particle size of 300nm and 0.5g of polyvinyl pyrrolidone to the sol, and ball mill it at room temperature at a speed of 250rpm for 4h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 5mL of 0.5mol / L calcium chloride solution on the upper surface of the slurry to form a stable film, and then pour 100mL of 0.5mol / L calcium chloride solution on the top of the film, let it stand for 8h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in 1mol / L gluconolactone solution for 8h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed again with deionized water, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a vacuum heat treatment furnace, and the temperature was raised to 620°C at a rate of 2°C / min under a vacuum degree lower than 0.1Pa, and the temperature was kept for 4 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and the surface image is shown in FIG. Figure 5 As shown, the pore size is 100 μm.

[0056] Example 6

[0057] Take 1g of sodium alginate and add it to 100mL of deionized water. Stir it magnetically at 50℃ for 1h to completely dissolve the sodium alginate and obtain a sol. Add 3g of silicon powder with a particle size of 500nm and 0.3g of polyethylene glycol to the sol, and ball mill it at room temperature at a speed of 200rpm for 3h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 20mL of 6.0mol / L calcium chloride solution evenly on the top of the film, let it stand for 6h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in a 1mol / L gluconolactone solution for 6h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a vacuum heat treatment furnace, and the temperature was raised to 600°C at a rate of 2°C / min under a vacuum degree lower than 0.1Pa, and the temperature was kept for 3 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and the surface image is shown in FIG. Figure 6 As shown, the pore size is approximately 40 μm.

[0058] Example 7

[0059] Take 1g of sodium alginate and add it to 100mL of deionized water. Stir it magnetically at 50℃ for 1h to completely dissolve the sodium alginate and obtain a sol. Add 3g of silicon powder with a particle size of 500nm and 0.3g of polyethylene glycol to the sol, and ball mill it at room temperature at a speed of 200rpm for 3h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 5mL of 2.0mol / L ferrous chloride solution on the upper surface of the slurry to form a stable film, and then pour 25mL of 2.0mol / L ferrous chloride solution on the top of the film, let it stand for 6h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in 1mol / L gluconolactone solution for 6h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a vacuum heat treatment furnace, and the temperature was raised to 600°C at a rate of 2°C / min under a vacuum degree lower than 0.1Pa, and the temperature was kept for 3 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and the surface image is shown in FIG. Figure 7 As shown, the pore size is approximately 40 μm.

[0060] Example 8

[0061] Take 1g of sodium alginate and add it to 50mL of deionized water. Stir it magnetically at 50℃ for 2h to completely dissolve the sodium alginate and obtain a sol. Add 2g of silicon powder with a particle size of 100nm and 0.2g of silane coupling agent to the sol, and ball mill it at room temperature at a speed of 225rpm for 4h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 10mL of 10.0mol / L calcium chloride solution evenly on the upper surface of the slurry, let it stand for 4h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in a 1mol / L gluconolactone solution for 6h to replace the calcium ions involved in the reaction with hydrogen ions, so that the wet blank shrinks and improves the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a tubular furnace, heated to 620°C at a rate of 2°C / min under argon flow, kept warm for 4 hours to complete the debinding, and then cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and its surface image is shown in the figure. Figure 8As shown, the pore size is approximately 20 μm.

[0062] Example 9

[0063] Take 1g of sodium alginate and add it to 50mL of deionized water. Stir it magnetically at 50℃ for 2h to completely dissolve the sodium alginate and obtain a sol. Add 2g of silicon powder with a particle size of 100nm and 0.2g of silane coupling agent to the sol, and ball mill it at room temperature at a speed of 225rpm for 4h to stably disperse and suspend the silicon powder in the sol to obtain a sodium alginate / silicon powder slurry. Transfer the slurry to the mold, spray 5mL of 0.5mol / L copper chloride solution on the upper surface of the slurry to form a stable film, and then pour 50mL of 0.5mol / L copper chloride solution on the top of the film, let it stand for 6h to wait for gelation to complete, and obtain a wet blank after demolding. Wash the wet blank with deionized water to remove unreacted calcium ions, and then soak the wet blank in 1mol / L gluconolactone solution for 6h to replace the copper ions involved in the reaction with hydrogen ions to shrink the wet blank and improve the mechanical strength of the final product. The wet blank was washed with deionized water again, and then transferred to a freeze dryer, and freeze-dried at -50°C and 1Pa for 48 hours to obtain a porous silicon dry blank. The dry blank was transferred to a tubular furnace, heated to 620°C at a rate of 2°C / min under argon flow, kept warm for 4 hours to complete the debinding, and cooled to room temperature at a rate of 2°C / min to obtain a porous silicon material. The micromorphology of the sample was characterized using a scanning electron microscope, and the surface image is shown in the figure. Fig. 9 As shown, the pore size is approximately 20 μm.

[0064] Although several embodiments of the present invention have been given herein, those skilled in the art should understand that the embodiments of the present invention may be modified without departing from the spirit of the present invention. The above embodiments are merely exemplary and should not be used as a limitation on the scope of the present invention.

Claims

1. A method for preparing a honeycomb micron-sized porous silicon material, characterized in that: The steps include: 1) adding sodium alginate to deionized water and stirring for 1 to 2 hours to completely dissolve the sodium alginate to obtain a sodium alginate sol; 2) adding silicon powder and a suspending agent to the sodium alginate sol, and ball milling for 3 to 6 hours to obtain a slurry in which silicon powder is stably suspended; 3) injecting the slurry obtained in step 2) into a mold, introducing a sufficient amount of gelling agent on the upper surface of the slurry, and demolding after gelation is completed to obtain a wet blank; 4) washing the wet blank obtained in step 3) in deionized water to remove unreacted metal ions, soaking the wet blank in a gluconolactone solution for 6 to 12 hours to allow hydrogen ions to replace the metal ions involved in the reaction, washing the wet blank with deionized water to remove unreacted hydrogen ions, and freeze-drying the wet blank to obtain a porous silicon dry blank; 5) The dry blank obtained in step 4) is subjected to high temperature debinding to obtain a porous silicon material.

2. The preparation method according to claim 1, wherein In step 1), the concentration of sodium alginate in the solution is 0.5-3%.

3. The preparation method according to claim 1, wherein The stirring in step 1) is carried out at a temperature of 50-60° C. using a magnetic stirrer.

4. The preparation method according to claim 1, wherein The particle size of the silicon powder in step 2) is 0.1-1 μm, and the content of the silicon powder in the sol is 0.5-20%.

5. The preparation method according to claim 1, wherein In step 2), the ball milling is performed at room temperature at a rotation speed of 200 to 300 rpm.

6. The preparation method according to claim 1, wherein The type of the suspending agent in step 2) is one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyacrylate and silane coupling agent. Preferably, the mass of the suspending agent is 5-10% of the mass of the silicon powder.

7. The preparation method according to claim 1, wherein The gelling agent in step 3) is one or more of calcium chloride, zinc chloride, copper sulfate, nickel chloride, nickel nitrate, cobalt chloride and ferrous chloride solution, the solution concentration is 0.05-10 mol / L, and the gelling reaction time is 3-12 hours.

8. The preparation method according to claim 1, wherein The freeze-drying process conditions in step 4) are a temperature of -65 to -50°C, a vacuum degree of less than 1 Pa, and a freeze-drying time of 24 to 48 hours.

9. The preparation method according to claim 1, wherein: The high-temperature debinding process in step 5) is carried out in a tubular furnace or a vacuum heat treatment furnace, the debinding atmosphere is an inert gas circulation or a vacuum environment, the debinding temperature is 600-650°C, the debinding time is 3-5h, and the heating and cooling rates are 1-2°C / min.

10. A honeycomb micron-sized porous silicon material, characterized in that: The porous silicon material is prepared by the method described in any one of claims 1 to 7. The porous silicon material has regularly arranged honeycomb-shaped micron-level through holes, a porosity of 30 to 95%, and a pore size range of 10 to 300 μm.

Citation Information

Patent Citations

  • Micron-order honeycomb ceramic and method for adjusting and controlling pore diameter and size of pore wall of micron-order honeycomb ceramic

    CN103274704B